2022
DOI: 10.1021/acs.jced.2c00145
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Adsorption by Porous Materials: From Chemistry to Practical Applications

Abstract: In recent years, the deployment of chemically stable physisorbents in various water sorption-related applications has received significant attention. Depending on their structural features, different types of porous sorbents manifest distinct shapes of water sorption isotherms. The translation of water sorption profiles of adsorbents into appropriate practical applications is yet to be established. This Review gives an overview of the water adsorption studies conducted on different hydrolytically stable porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 303 publications
0
18
0
Order By: Relevance
“…The values of a H2ORH90 ranged from 272 to 445 mg/g for CH=O and CH 2 OH groups containing networks while a H2ORH90 was only 36 mg/g for P(pentyne/TEB 3:1). The data in Table 2 and the character of the isotherms in Figure 5 indicated that two processes were most likely involved in the capture of water vapour in the functionalized networks: (i) adsorption of H 2 O molecules on the surface of pores accompanied by trapping of H 2 O in narrow micropores and (ii) capillary condensation of water in larger pores [ 55 ] (see Scheme 2 ). At lower RH values, the adsorption and filling of narrow micropores prevailed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of a H2ORH90 ranged from 272 to 445 mg/g for CH=O and CH 2 OH groups containing networks while a H2ORH90 was only 36 mg/g for P(pentyne/TEB 3:1). The data in Table 2 and the character of the isotherms in Figure 5 indicated that two processes were most likely involved in the capture of water vapour in the functionalized networks: (i) adsorption of H 2 O molecules on the surface of pores accompanied by trapping of H 2 O in narrow micropores and (ii) capillary condensation of water in larger pores [ 55 ] (see Scheme 2 ). At lower RH values, the adsorption and filling of narrow micropores prevailed.…”
Section: Resultsmentioning
confidence: 99%
“…The water adsorption/desorption isotherms on functionalized networks were well reproducible, as evident from Figure S6 in Supplementary Materials showing the isotherms for two consecutive H 2 O adsorption/desorption cycles. Water capture capacities when RH = 90% of P(M1/TEB 1:1)H and P(M2/TEB 1:1)H, a H2ORH90 = 445 mg/g and a H2ORH90 = 422 mg/g, respectively, corresponded to the highest values reported for sorbents of the porous polymer-type [ 19 , 55 ]. For example, polyphenylene-type POPs functionalized with NH 2 and NO 2 groups exhibited water capture capacities from 290 to 350 mg/g (RH = 97%, 297 K) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…put forward prospects [13,16,22] . However, how to improve the transport speed of water molecules in the adsorbent micropores should be discussed, which is expected to promote the further development of psaAWH.…”
Section: Introductionmentioning
confidence: 99%
“…However, how to improve the transport speed of water molecules in the adsorbent micropores should be discussed, which is expected to promote the further development of psaAWH. In addition, other reviews have less attention to the emerging materials such as covalent organic frameworks (COFs) and crystalline porous organic salts (CPOSs) [5,[22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption curve partly resembles that of type F−II isotherms for flexible microporous materials (suddenly opening from small pores to larger pores). 41,42 Replacing DEF solvates with CHCl 3 resulted in a pore-shape change to compressed rhombic apertures but with retention of the MOF topology. Notably, the CO 2 isotherms of the CHCl 3 -exchanged sample exhibit a standard type I adsorption with slight hysteresis, indicating that MOF 1 is a metastable phase and could readily transform into a more stable phase upon solvate exchange.…”
mentioning
confidence: 99%